Social Media and Well-Being: Pitfalls, Progress, and Next Steps. Issue 1 (January 2021) - Kross, Ethan; Verduyn, Philippe; Sheppes, Gal; Costello, Cory K.; Jonides, John; Ybarra, Oscar
Abstract : Within a relatively short time span, social media have transformed the way humans interact, leading many to wonder what, if any, implications this interactive revolution has had for people's emotional lives. Over the past 15 years, an explosion of research has examined this issue, generating countless studies and heated debate. Although early research generated inconclusive findings, several experiments have revealed small negative effects of social media use on well-being. These results mask, however, a deeper set of complexities. Accumulating evidence indicates that social media can enhance or diminish well-being depending on how people use them. Future research is needed to model these complexities using stronger methods to advance knowledge in this domain. Highlights: Social media has revolutionized how humans interact, providing them with unprecedented opportunities to satisfy their social needs. An explosion of research has examined whether social media impacts well-being. First- and second-generation studies examining this issue yielded inconsistent results. An emerging set of third-generation experiments has begun to reveal small but significant negative effects of overall social media use on well-being. The results of these experiments mask the complexities characterizing the relationship between social media and well-being. Whether it enhances or diminishes well-being depends on how and why people use it, as well as who uses it. People use social media for different reasons (e.g., to manage impressions, to share emotions), which influence how it impacts their own and other people's well-being.